IMMU-26. RADIATION AND TEMOZOLOMIDE UP-REGULATES CD70 EXPRESSION AND ENHANCES CAR T- CELL RECOGNITION IN GBM - Na, Meng (Neuro Oncol, 2019)
BACKGROUND: Glioblastoma (GBM) is a recalcitrant brain cancer in the clinic. The therapeutic effect of using standard care (SC), such as surgery, radiation and/or temozolomide (TMZ) is dismal. CAR T-cell therapy has been increasingly recognized in the field as an innovative therapeutic approach for this malignancy. We identified CD70 as a glioma marker, and show that CD70CAR T cells recognize CD70+ GBMs and mediated regression of established tumors. Since recurrent GBMs that had been heavily treated by the SC treatments expressed a relatively higher level of CD70 than primary tumors, we thus hypothesize that these modalities may help to enhance the expression of CD70 and therapeutic effect of the CD70CAR T cell therapy in GBM. OBJECTIVE: To determine if radiation or TMZ treatments could influence the CD70 expression of GBM, and the CD70CAR T-cell recognition. METHODS: CD70 expression on GBM cell lines, including primary GBMs (CD70+ or CD70-) and U87 (CD70+), were assessed after treating with escalated doses of irradiation or TMZ. The protein and gene expression were determined by FACS or qRT-PCR analysis, respectively, at 4, 24, 48, and 120 hours post irradiation or TMZ treatment. Tumor recognition post-treatment was also carried out. Paired samples using an RNA-seq dataset from TCGA before and after tumor recurrence were evaluated for the CD70 expression. RESULTS: CD70 expression was markedly increased by irradiation or TMZ treatment in a dose-dependent manner (beginning at 24 hours) in vitro in CD70+ GBMs, and a slight increased in the CD70(—) GBMs. The treatments enhance CD70CAR T cell recognition. Up-regulation of CD70 was found in the paired GBM patients. CONCLUSION: This study demonstrates that the irradiation or TMZ treatment significantly up-regulates CD70 expression on GBMs and the CAR-T cell recognition, providing a rationale to combine CD70CAR-T cell therapy with SC for enhanced therapeutic efficacy in GBM.